Evaluación de la demanda de desplazamiento de un edificio de acero con pórticos arriostrados a pandeo restringido mediante un análisis estático no lineal (2021)
The use of buckling restrained braced frames is common in countries like the United States. However, in Colombia the use of this seismic resistance system in steel buildings is not very common. To study the behavior of this type of buildings in the Colombian territory, a study was carried out that evaluates the demand of displacement for a building of this type through non-linear static analysis. The structure in question is 30 meters high and has 10 stories, it is located in Pasto-Nariño, an area of high seismic threat in Colombia. Based on NSR-10, the building and its foundation were preliminarily designed, taking into account a linear analysis. Subsequently, the non-linear static analysis of the structure was carried out. The result of these analyzes allowed to conclude that the performance level of the structure was satisfactory, while deficiencies were found in the foundation.